EXTRACTION OF NAPHTHENIC ACIDS FROM LIQUID HYDROCARBON USING IONIC LIQUIDS - KAMARUDIN, HASIAH (2013)
This study focuses on the extraction performance of selected Imidazolium type ionic liquids on naphthenic acids namely benzoic (aromatic), 2-cyclohexylacetic acid and n-hexanoic (aliphatic) acids from a dodecane. Eight imidazolium ionic liquids were used in the liquid-liquid extraction study which comprise of l-n-butyl-3- methylimidazolium [C4mim] and l-ethyl-3-methylimidazolium [C2mim] as the cation, coupled with six different anions namely thiocyanate [SCN], octylsulfate [OCS], diethylphosphate [DbFj, tns(pentafiuoroethyl)trifluorophosphale [FAP], acetate [AC] and trifluoromethanesulfonate [OTF]. The liquid-liquid extraction study was conducted using experimental approach and the finding on its performance is compared against the prediction calculated using molecular simulation approach based on Conductor like Screening MOdel for Real Solvents (COSMO-RS) method.